Aqueous Zn²⁺/Na⁺ dual-salt batteries with stable discharge voltage and high columbic efficiency by systematic electrolyte regulation - Wang, Chunli (2022)
While aqueous Zn-Na hybrid batteries have garnered widespread attention because of their low cost and high safety, it is still challenging to achieve long cycle-life and stable discharge-voltage due to sluggish reaction kinetics, zinc dendrite formation, and side reactions. Herein, we design a Zn2+/Na+ dual-salt battery, in which sodiation of the NVP cathode favors zinc intercalation under an energy threshold, leading to decoupled redox reactions on the cathode and anode. Systematic investigations of the electrolyte effects show that the ion intercalation mechanism and the kinetics in the mixture of triflate- and acetate-based electrolytes are superior to those in the common acetate-only electrolytes. As a result, we have achieved fast discharging capability, suppressed zinc dendrites, a stable discharge voltage at 1.45 V with small polarization, and nearly 100% Columbic efficiency in the dual-salt mixture electrolyte with optimized concentration of 1 M Zn(OAc)2 + 1 M NaCF3SO3. This work demonstrates the importance of electrolyte regulation in aqueous dual-salt hybrid batteries for the energy storage.